THE IMPACT OF HUMAN ACTIVITIES ON ENVIRONMENTAL SUSTAINABILITY - Inbit, Mohammed Jabar Odah; alkolany, Mohamed abdulhassan eliwi; Kazem, Ahmed Abd Ali; Hussein, Hussain Hamza; Brism, Raed Abd AL-kadum mageed (Journal of Medical Genetics and Clinical Biology, 2024)
-